A new strategy to mitigate herbicide contamination: decentralized electrochemical treatment of real glyphosate-contaminated wastewater - Mandelli, Cecília Montanha; Sgarbi, Ricardo; Oliveira, Kaíque Souza Gonçalves Cordeiro; Oliveira, Gabriel Palace; Ruotolo, Luis Augusto Martins (Universidade Federal de São Carlos, 2026)
Electrochemical treatment of wastewater is a promising way to reduce organic pollutant loads. The herbicide glyphosate is extensively used in agriculture, so the washing of its containers generates substantial volumes of harmful effluents. This study investigates the optimal conditions for electrolysis of a real glyphosate-contaminated wastewater, considering treatment time, energy consumption, and operational costs. Experiments were conducted using an electrochemical flow reactor fitted with a boron-doped diamond (BDD) anode. A factorial design was employed to evaluate the effects of current density (10–30 mA cm−2) and initial organic load (100–300 mg TOC L−1). Monitoring was performed of total organic carbon (TOC), chemical oxygen demand (COD), and cell potential. The use of a low-cost turbulence promoter (plastic mesh) improved mass transfer, enhanced mineralization efficiency, and reduced energy consumption, while the control of temperature had a minimal influence. Application of a current density of 30 mA cm−2 provided the best balance between treatment duration and energy efficiency. Predictive models were developed to estimate the electrolysis time and specific electrochemical energy consumption (SEEC). Operational cost related to electrochemical energy consumption ranged from USD 1.71 m−3 to USD 7.09 m−3, with values between USD 2.89 m−3 and USD 5.77 m−3 obtained for wastewater containing 300 mgTOC L−1 treated at 30 mA cm−2, demonstrating the feasibility of the process, even with a high organic load. These findings contribute to the development of optimized and cost-effective electrooxidation systems for the treatment of pesticide-contaminated effluents, supporting the sustainable management of agricultural wastewater.
Keywords: Boron-doped diamond; glyphosate; wastewater; turbulence promoter; mass transfer; 6. Água Potável e Saneamento